A path analysis approach on the factors of human development among Muslims in Nigeria - Oladapo, Ibrahim Abiodun; Ab Rahman, Asmak (Emerald, 2018)
Purpose: One area of concern for Islamic economics is the challenges and discrimination experienced in Muslim societies and the lower human development indices compared to the Western counterparts. It is possible that the application of the theory of Maqāsid al Sharī’ah (TMS) could provide some insight on the problems and probably offer some support to the policymaker on the direction to take. The purpose of this paper is to apply TMS to validate the factors of human development. Design/methodology/approach: The primary data were collected using a questionnaire. The target respondents were Muslims from Nigeria. Both stratified and purposeful random sampling techniques were used to collect the data, and the analyses were done by SPSS and AMOS statistical software. Findings: In validating factors that contribute to human development, TMS framework is used, and the model integrates five factors which are considered most likely to have influence on human development. The model proposes that individual factors such social justice and human rights have effects on the factors of human development. Originality value: This study provides understanding on the contributing factors to the persistent challenges of human development in predominantly Muslim settings. Previous research which has applied TMS focused more on its financial relevance and has not attempted to understand the situation and proffer solution.